Cerebrospinal Fluid Biomarkers in Cerebral Amyloid Angiopathy: New Data and Quantitative Meta-Analysis - Margraf, Nils G.; Jensen-Kondering, Ulf; Weiler, Caroline; Leypoldt, Frank; Maetzler, Walter; Philippen, Sarah; Bartsch, Thorsten; Flüh, Charlotte; Röcken, Christoph; Möller, Bettina; Royl, Georg; Neumann, Alexander; et al. (Frontiers in Aging Neuroscience, 2022)
Background: To evaluate the diagnostic accuracy of CSF biomarkers in patients with probable cerebral amyloid angiopathy (CAA) according to the Modified Boston criteria in a retrospective multicentric cohort. Methods: Aß40, Aß42, t-tau, and p-tau181 were measured in 31 patients with probable CAA, 28 patients with Alzheimer’s disease (AD), and 30 controls. Receiver-operating characteristics (ROC) analyses were performed for the measured parameters as well as the Aß42/40 ratio to estimate diagnostic parameters. A meta-analysis of all amenable published studies was conducted. Results: In our data Aß42/40 (AUC 0.88) discriminated best between CAA and controls while Aß40 did not perform well (AUC 0.63). Differentiating between CAA and AD, p-tau181 (AUC 0.75) discriminated best in this study while Aß40 (AUC 0.58) and Aß42 (AUC 0.54) provided no discrimination. In the meta-analysis, Aß42/40 (AUC 0.90) showed the best discrimination between CAA and controls followed by t-tau (AUC 0.79), Aß40 (AUC 0.76), and p-tau181 (AUC 0.71). p-tau181 (AUC 0.76), Aß40 (AUC 0.73), and t-tau (AUC 0.71) differentiated comparably between AD and CAA while Aß42 (AUC 0.54) did not. In agreement with studies examining AD biomarkers, Aß42/40 discriminated excellently between AD and controls (AUC 0.92-0.96) in this study as well as the meta-analysis. Conclusions: The analyzed parameters differentiate between controls and CAA with clinically useful accuracy (AUC > ~ 0.85) but not between CAA and AD. Since there is a neuropathological, clinical and diagnostic continuum between CAA and AD, other diagnostic markers, e.g. novel CSF biomarkers or other parameters might be more successful.